Pretreatment Patient Specific Quality Assurance and Gamma Index Variation Study in Gantry Dependent EPID Positions for IMRT Prostate Treatments. (5th March 2014) - Cyriac, Siji; Musthafa, M. M.; Ganapathi Raman, R.; Abdul Haneefa, K.; Hridya, V. T.
Abstract : Pretreatment quality assurance (QA) is a major concern in complex radiation therapy treatment plans like intensity modulated radiation therapy (IMRT). Present study considers the variations in gamma index for gantry dependent pretreatment verification and commonly practiced zero gantry angle verifications for ten prostate IMRT plans using two commercial medical linear accelerators (Varian 2300 CD, Varian Clinac iX). Two verification plans (the one with all fields at the actual treatment angles and one with all fields merged to 0 degree gantry angles) for all the patients were generated to obtain dose fluence mapping using amorphous silicon electronic portal imaging device (EPID). The gamma index was found depend on gantry angles but the difference between zero and the nonzero treatment angles is in the confidence level for clinical acceptance. The acceptance criteria of gamma method were always satisfied in both cases for two machines and are stable enough to execute the patient specific pretreatment quality assurance at 0 degree gantry angle for prostate IMRTs, where limited number of gantry angles are used.